Cutaneous cryptococcosis: an underlying immunosuppression? Clinical manifestations, pathogenesis, diagnostic examinations and treatment - Nowak, Marcela; Putynkowska, Anna; Barańska-Rybak, Wioletta; Czarnacka, Kamila; Dębska-Ślizień, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Due to constantly growing population of immunocompromised patients the fungi became a widespread threat to modern medicine. HIV carriers, solid organ transplant recipients constitute most of those patients. Cryptococcosis is a frequent cause of life-threatening infections, affecting mostly immunosuppressed patients. This article presents current knowledge on cryptococcal infections, including epidemiology, clinical aspects, diagnosis and recommended treatment. In reference to our patient, who developed a disseminated and fulminant subtype of the disease, we wanted to underline the need to examine patients thoroughly. The highest aim of those measures would be to avoid lethal consequences.